Gossypiboma a Diagnostic Dilemma or Medical Negligence A Case Report - Garg, M K; Zeya, M T; Garg, Uma; Goyal, Sunder; Yadav , Mukesh (Journal of Indian Academy of Forensic Medicine, 2014)
Gossypiboma or textiloma is a rare avoidable surgical disaster which has got medicolegal repercussions. It is a mass lesion due to a retained surgical cotton sponge surrounded by foreign-body reaction. The aim of this study was to review the literature on forgotten sponges to identify incidence, risk factors, mechanism of intraluminal migration and preoperative diagnostic modalities. A 50-year-old lady presented with palpable abdominal mass seventeen years after appendicectomy. A clinical diagnosis of mesenteric cyst was made. Ultrasound revealed a heterogeneous mass with variable echogenicity. On laparotomy, retained foreign body (cotton sponge) was found. Retained foreign body (RFB) should always be considered in the differential diagnosis of any postoperative patient who presents with pain, infection, or palpable mass or with unusual symptoms. Doctrine of ‘Res Ipsa Loquitur’ along with ‘discovery rule’ may be applied in some cases, depending on whether fact brought to the notice of the patient or relatives and grievance of patient with the doctor or hospital as the case may be. Since these facts comes to notice after a long gape, cause and effect relationships is very difficult to prove.